Novel potential biomarkers for severe alcoholic liver disease - Huang, Jia; Yu, Jiachi; Wang, Jianan; Liu, Jiayu; Xie, Wei; Li, Ruibing; Wang, Chengbin (Frontiers in Immunology, 2022)
Background Alcoholic liver disease (ALD) is a leading cause of advanced liver disease, but slighter clinical symptoms in the early stage frequently result in its delayed diagnosis and therapy. Invasive liver biopsy, the gold standard for diagnosing ALD, is unsuitable for repetitive performance. This study aims to identify potential serum biomarkers that could contribute to non-invasive disease screening and monitoring. Methods Label-free LC-MS/MS quantitative proteomics were performed to identify differentially expressed proteins in the discovery cohort, followed by bioinformatics analysis based on the KEGG, GO, and String databases. Prioritized proteins were validated subsequently by quantitative assays. The area under the receiver operating characteristic curve (AUROC) was used to assess the diagnosis performance of potential biomarkers. Results 161 differentially expressed proteins were identified in the discovery cohort, of which 123 were up-regulated and 38 were down-regulated. B2M, IGFALS, and IGFBP3 were evaluated and all demonstrated excellent diagnosis performance with the AUROCs of over 0.9 when distinguishing severe ALD from HC. The AUROC of B2M was 0.7131, IGFBP3 0.8877, and IGFALS 0.9896 in differentiating severe ALD from non-severe ALD group to indicate disease severity. Multiple combinations of these biomarkers were superior to the existing liver fibrosis evaluation indexes to monitor disease progression with AUROCs of over 0.9. Conclusion This proteomic study identified 3 novel candidate proteins as promising circulating biomarkers for clinical diagnosis and disease progression, and also provided the proteomic atlas for ALD pathophysiological mechanisms.